Potential of Tithonia diversifolia Hemsl. A Gray as forage for the production of dairy cows. - Gallego-Castro, Luis Alberto (2014)
The objective of this study was to analyze the potential use of Tithonia diversifolia (Hemsl.) A. Gray (Mexican sunflower) in dairy cattle feeding in the Colombian high tropics. Key terms were chosen to search for information and from them this we discussed and analyzed several publications, allowing an approach to the problem proposed. It is common that in the high-tropic dairy farms of Colombia the main component of the cattle’s diet is the Kikuyu grass (Pennisetum clandestinum). Given its characteristics of high levels of Nitrogen, low levels of fiber and dry matter, it is common that this diet causes a negative energetic balance in the most productive cows. In order to sustain production in those cases, sometimes it is required to supplement the forage with commercial rations, which have high protein levels, and are mainly composed by cereals. The nutritional requirements of these production systems demand strategies that allow the improvement and quality of fodder offer, and to reduce the dependence on commercial rations or at least to ease the inclusion of others that improve animal performance. From this analysis, the benefits and potential use of T. diversifolia in feeding high producing dairy cows were recognized. Considering the content of protein, soluble carbohydrates and tannins, the forage of this shrub may have a positive impact on intensive dairy farming systems and could have potential to be incorporated into dietary supplements.